Bryophytes in the hydrological cycle and climate change implications : A case study of La Réunion cloud forest - Cardoso, Anabelle Williamson (Department of Biological Sciences, 2017)
Bryophytes are able to intercept atmospheric water over the entire surface of their shoot and, once intercepted, this water forms a vital part of the hydrological cycle of their surrounding ecosystems. To investigate the role of bryophytes in the hydrological cycle, our study, conducted in the biodiversity hotspot of the tropical montane cloud forest of La Réunion, focused on two leafy liverwort species, Mastigophora diclados and Bazzania decrescens. We evaluated liverwort biomass, water storage capacity, atmospheric or cloud water interception, and photosynthetic response to desiccation. We found that B. decrescens stored approximately double the mean and maximum litres of water per hectare despite occupying less than half the volume of M. diclados. Despite this decreased water storage capacity, we found that M. diclados had a greater ability to intercept atmospheric moisture than B. decrescens, which had similar interception ability to the control. These interception abilities affected water flux in the two liverwort species. We found that this variation in water flux had an effect on photosynthesis. Both species displayed a significant relationship between photosynthesis and water content. We found that both species showed a loss of photosynthesis at very low and very high water contents with the optimal water content for photosynthesis corresponding to the in situ water content of the liverworts. The abundance of both species and their cloud water interception ability together with the wide range of photosynthetic tolerance of M. diclados and the large water storage capacity and slow desiccation rate of B. decrescens make both liverwort species ecologically important in the forest's hydrological cycle. Anthropogenic climate change threatens this ecosystem as the cloud that these species are so dependent on is predicted to lift. Our findings tie the liverworts very closely to their environment and therefore show support for the idea that bryophytes are excellent early warning signals for predicted climate changes.